A charity or a right?: Repatriation of disabled ex-servicemen in Western Australia, post World War I - Summers, Sue (Black Swan Press, 2014)
This chapter focuses on the troubled repatriation of disabled ex-servicemen in Western Australia, through a case study of Trooper Frank Leear Bolger who served with the 10th Light Horse in Gallipoli for nine months before being discharged as totally incapacitated and unfit for further service. Bolger is typical of many WWI soldiers who were promised much within the rolling recruitment campaigns across Western Australia that drew large numbers of men into the war effort. On their return they were confronted with a downturn of the economy and jobs shortages compounded by the vagaries and inconsistencies of the Repatriation Scheme in WA. As Bolger pointed out in a letter to the Department of Repatriation in Perth in 1921: “According to the terms I enlisted under in 1914 I don’t see why it [war pension] should be liable to suspension as it is not charity, but a right”. This and other rights – outlined in the rhetoric and enlistment policies of World War 1 – were all too often disregarded by the Repatriation Office in Perth, and often in contravention of instructions from its Melbourne headquarters. This chapter discusses Bolger and similar cases with a clear focus on the post-WWI repatriation policies and schemes for disabled ex-servicemen in WA, an often understudied aspect in the literature on returning soldiers.